Pacing strategy in short cycling time trials - de Jong, J.; van der Meijden, L.; Hamby, S.; Suckow, S.; Dodge, C.; de Koning, J. J.; Foster, C. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To reach top performance in cycling, optimizing distribution of energy resources is crucial. The purpose of this study was to investigate power output during 250-m, 500-m, and 1000-m cycling time trials and the characteristics of the adopted pacing strategy. Methods: Nine trained cyclists completed an incremental test and 3 time trials that they were instructed to finish as quickly as possible. Preceding the trials, peak power during short sprints (PPsprint) and gross efficiency (GE) were measured. During the trials, power output and oxygen consumption were measured to calculate the contribution of the aerobic and anaerobic energy sources. After the trial GE was measured again. Results: Peak power during all trials (PPTT) was lower than PPsprint. In the 250-m trial the PPTT was higher in the 1000-m trial (P = .008). The subjects performed a significantly longer time at high intensity in the 250-m than in the 1000-m (P = .029). GE declined significantly during all trials (P < .01). Total anaerobically attributable work was less in the 250-m than in the 500-m (P = .015) and 1000-m (P < .01) trials. Conclusion: The overall pacing pattern in the 250-m trial appears to follow an all-out strategy, although peak power is still lower than the potential maximal power output. This suggests that a true all-out pattern of power output may not be used in fixed-distance events. The 500-m and 1000-m had a more conservative pacing pattern and anaerobic power output reached a constant magnitude.